2017
DOI: 10.1371/journal.pgen.1006669
|View full text |Cite
|
Sign up to set email alerts
|

The transjugation machinery of Thermus thermophilus: Identification of TdtA, an ATPase involved in DNA donation

Abstract: In addition to natural competence, some Thermus thermophilus strains show a high rate of DNA transfer via direct cell-to-cell contact. The process is bidirectional and follows a two-step model where the donor cell actively pushes out DNA and the recipient cell employs the natural competence system to take up the DNA, in a hybrid transformation-dependent conjugation process (transjugation). While the DNA uptake machinery is well known as in other bacterial species that undergo transformation, the pushing step o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 46 publications
0
54
0
Order By: Relevance
“…Still more surprising was the requirement of a fully active natural competence system in the recipient cells, in such a way that mutants deficient in virtually any described component of the DTA could serve only as DNA donor, a property that led to proposal of the term transjugation (transformation-dependent conjugation) (Blesa et al, 2017). Further parenthood analysis experiments, in which combinations of non-competent mutants were used, confirmed that the DNA-donation machinery was independent of the competence apparatus, both present in the same bacteria, implying a two-step ("push and pull") model for transjugation.…”
Section: ! 28mentioning
confidence: 99%
See 3 more Smart Citations
“…Still more surprising was the requirement of a fully active natural competence system in the recipient cells, in such a way that mutants deficient in virtually any described component of the DTA could serve only as DNA donor, a property that led to proposal of the term transjugation (transformation-dependent conjugation) (Blesa et al, 2017). Further parenthood analysis experiments, in which combinations of non-competent mutants were used, confirmed that the DNA-donation machinery was independent of the competence apparatus, both present in the same bacteria, implying a two-step ("push and pull") model for transjugation.…”
Section: ! 28mentioning
confidence: 99%
“…The search for putative components of the DNApushing system led to the identification of transjugation donor translocase A (TdtA), a protein belonging to the FtsK-HerA family of DNA translocase-helicases. Its mutation impaired the ability of the cell to act as a donor in transjugation, without significant effect on natural competence or any other phenotypic trait (Blesa et al, 2017). Purified recombinant TdtA was subsequently shown to form hexameric rings in the presence of ATP, with a central pore wide enough to accommodate dsDNA, resembling the TraB protein encoded by conjugative plasmids of Streptomyces spp.…”
Section: ! 28mentioning
confidence: 99%
See 2 more Smart Citations
“…Inferential and comparative assays were performed when necessary and include Student’s t -tests, Kruskal-Wallis one-way analysis, Wilcoxon tests, and one-way analysis of variance (ANOVA) test, as described [15]. …”
Section: Methodsmentioning
confidence: 99%